Evaluation of policy synergy in coastal ocean pollution prevention and control: The case from China - Yao, Chengyan; Sun, Mengge; Liu, Lin (Frontiers in Marine Science, 2023)
In recent years, the Chinese central government and coastal provincial governments have promulgated a series of Coastal Ocean Pollution Prevention and Control Programs (COPPCP). Whether the government’s COPPCP can achieve policy synergy will affect the level of marine pollution governance. This study constructs a two-dimensional assessment framework of policy “subject department”–”content theme” and conducts a comprehensive evolution of policy synergy from objective, process, and state perspectives. From the subject department dimension, the study used social network analysis to find that interdepartmental collaboration was not done well overall. The policy synergy process is difficult to be guaranteed. Meanwhile, the structure of departmental synergy networks in different provinces shows differences and can be divided into three types of governments with single-core, multi-core, and vertical synergy. In the content synergy dimension, it was found by the Chinese Bidirectional Encoder Representations from Transformers-Whole Word Masking (BERT-WWM) model that the policy content is mainly focused on four themes of marine ecological protection (MEP), marine pollution control (MPC), land-based pollution reduction (LPR), and safeguard measures (SAM). The three types of governments show different performances on the four theme synergies. The governments perform well in the objective synergy; however, it is difficult for them to agree on the policy tool synergy, and the status of policy synergy is difficult to maintain. This paper adopts the BERT-WWM model instead of the manual coding method in the previous policy content analysis, enhancing the evaluation’s objectivity. The study results will provide a reference for further improving marine pollution governance systems in developing countries.